Correlates of Knowledge and Adoption Behaviour of Farmers with their Profile Characteristics : An Analysis of Chrysanthemum Growers in Mandya District of Karnataka - Mamathalakshmi,; Nagabhushanam, N. K.; Nataraju, M. S.; Surendra, H. S.; Krishnamurthy, B.; G.T., Sowmyashree (Indian Journal of Extension Education, 2013)
The present investigation was conducted in Mandya district of Karnataka during the period 2009-2010. The chi-square  value clearly showed that age, area under chrysanthemum, family size and family type had significant association at one  per cent with their adoption behaviour. While the variables like occupational status, economic motivation, mass media  utilization and management orientation had significant association at five per cent with their adoption behaviour. Further,  study indicated that inadequate irrigation facilities, limited and irregularity of power supply, lack of finance / credit  facility were the main adoption constraints perceived by the farmers in chrysanthemum cultivation.
Keywords: Chrysanthemum; adoption behaviour; chi-square; constraints